2014
DOI: 10.15446/abc.v19n3.41366
|View full text |Cite
|
Sign up to set email alerts
|

REPRODUCTION AND CONSERVATION OF THE MAGDALENA RIVER TURTLE (Podocnemis lewyana) IN THE CLARO COCORNÁ SUR RIVER, COLOMBIA

Abstract: Citation / Citar este artículo como: Ceballos CP, RomeRo i, Gómez-saldaRRiaGa C, miRanda K. Reproduction and conservation of the magdalena River turtle (Podocnemis lewyana) in the Claro Cocorná sur River, Colombia. acta biol. Colomb. 2014;19(3):393-400. ABSTRACTThe Magdalena River Turtle, Podocnemis lewyana, is an endangered and endemic turtle from Colombia. Among the most important information needed to conserve endangered species is to identify, monitor, and protect the sites used by the species to reproduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…This is, the pivotal temperature of 33.4 °C produces both sexes in similar proportions, while higher temperatures produce mainly females and lower temperatures produce mainly males . Its reproductive cycle has not been studied in detail, however it is known that there are two nesting seasons: between December and March, and between June and August (Gallego-García and Castaño-Mora, 2008;Ceballos et al, 2014). Its average clutch size varies between 20 to 22 eggs, with an egg weight varying between 18-38 g and an egg size between 31-50 mm long x 21-44 mm width (Páez et al, 2012;Ceballos et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This is, the pivotal temperature of 33.4 °C produces both sexes in similar proportions, while higher temperatures produce mainly females and lower temperatures produce mainly males . Its reproductive cycle has not been studied in detail, however it is known that there are two nesting seasons: between December and March, and between June and August (Gallego-García and Castaño-Mora, 2008;Ceballos et al, 2014). Its average clutch size varies between 20 to 22 eggs, with an egg weight varying between 18-38 g and an egg size between 31-50 mm long x 21-44 mm width (Páez et al, 2012;Ceballos et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…For the turtle species, egg size can be determined by biological patterns of females, mainly related to their age, among other factors. Because these animals do not have parental care, the apparent energetic effort employed for reproduction can ensure better development of the offspring; thus, larger eggs may have greater hatching success and generate larger neonates (Valenzuela, 2001;Loehr et al, 2004, Warner et al, 2010Ceballos et al, 2014). Conditions of soil moisture and temperature that cause water loss in the egg may lead to a lower vitelline absorption and, then, generate smaller neonates (Ferreira-Junior, 2009a;FerreiraJunior, 2009b).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies (Fachín-Terán, 1993;Fachín-Terán et al, 1995;Rebelo and Pezzuti, 2000;Fachín-Terán and Von Mulhen, 2003;Fachín-Teran et al, 2004;Caputo et al, 2005;Fachín-Terán and Von Mulhen, 2006;Ceballos et al, 2014) on the influence of egg collection, adult chelonians hunting and effects of habitat destruction reported that the decline of chelonians populations is more strongly associated with increased activities that alter mainly the landscapes of Amazon floodplains. In the Araguari river basin (eastern Amazon), the nesting of P. unifilis occurs from September to November, eggs hatching occurrs in December and the mean incubation period is of 63.5 ± 5.2 days.…”
Section: Introductionmentioning
confidence: 99%
“…Species with TSD are particularly vulnerable to climate change because higher temperatures could bias natural sex ratios (Janzen 1994;Neuwald and Valenzuela 2011). The TSP has not been studied in P. lewyana; yet, artificial incubation of eggs is a current conservation practice to avoid egg mortality in some populations (Romero 2011;Ceballos et al 2014b), and the effect that this may have on sex determination is unknown. Furthermore, the TSP is ideally evaluated based on embryonic stages (Yntema 1978(Yntema , 1979Bull and Vogt 1981;Pieau and Dorizzi 1981); however, such destructive sampling is not always possible in endangered species (Le Blanc et al 2012).…”
mentioning
confidence: 99%
“…We incubated eggs under temperatures that were 100% feminizing and 100% masculinizing in a different P. lewyana population (Páez et al 2009) to test whether sex ratios differed in our population (Ceballos et al 2014b) and to obtain a baseline for comparison with our shift experiments. We estimated the onset and duration of the TSP using 6 shift-twice treatments (masculinizing-feminizing-masculinizing temperatures) as described below.…”
mentioning
confidence: 99%